2013
DOI: 10.1111/nph.12270
|View full text |Cite
|
Sign up to set email alerts
|

The Phytophthora parasitica RXLR effector Penetration‐Specific Effector 1 favours Arabidopsis thaliana infection by interfering with auxin physiology

Abstract: Summary Pathogenic oomycetes have evolved RXLR effectors to thwart plant defense mechanisms and invade host tissues. We analysed the function of one of these effectors (Penetration‐Specific Effector 1 (PSE1)) whose transcript is transiently accumulated during penetration of host roots by the oomycete Phytophthora parasitica. Expression of PSE1 protein in tobacco (Nicotiana tabacum and Nicotiana benthamiana) leaves and in Arabidopsis thaliana plants was used to assess the role of this effector in plant physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 62 publications
0
53
0
Order By: Relevance
“…Hence, six of the 14 sequences encoding RXLR effectors present on the oligoarray were present in cluster I. One of these six sequences corresponded to the PSE1 effector, which has recently been demonstrated to contribute to P. parasitica pathogenicity [38]. The expression patterns of sequences encoding cytoplasmic (RXLR and CRN) effectors are presented in Figure 3B.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence, six of the 14 sequences encoding RXLR effectors present on the oligoarray were present in cluster I. One of these six sequences corresponded to the PSE1 effector, which has recently been demonstrated to contribute to P. parasitica pathogenicity [38]. The expression patterns of sequences encoding cytoplasmic (RXLR and CRN) effectors are presented in Figure 3B.…”
Section: Resultsmentioning
confidence: 95%
“…These authors suggested a relay between these successive waves, interfering with plant immunity at various levels. We have shown that the PSE1 effector, which is transiently expressed during penetration, can interfere with auxin physiology to facilitate plant infection [38]. Additional functional analyses of effectors transiently expressed during the onset of infection are required to determine whether this specific set of proteins plays a particular role in modulating plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a RXLR effector of P. parasitica PSE1, identified in a cDNA library for the penetrating stage of P. parasitica (Kebdani et al 2010), was proved to favor the pathogen infection by modulating the auxin accumulation during the penetration process (Evangelisti et al 2013). …”
Section: The Molecular Basis Of Pathogenesismentioning
confidence: 99%
“…P. sojae AVR3b, which has NADH and ADP-ribose pyrophosphorylase activity, manipulates host immunity by interfering with effector-triggered immunity (Dong et al, 2011). The Phytophthora parasitica RXLR effector PENETRATION-SPECIFIC EFFECTOR1 promotes colonization by impeding host auxin physiology (Evangelisti et al, 2013). The P. infestans RXLR effector IPI-O1 disrupts the integrity of adhesions between the plasma membrane and the cell wall and uses the membrane-spanning lectin receptor kinase LecRK-I.9 as a host target (Bouwmeester et al, 2011).…”
mentioning
confidence: 99%